Peripartum cardiomyopathy presenting with repetitive monomorphic ventricular tachycardia - FAK, ALİ SERDAR (WILEY, 2004)
GEMICI, G., ET AL.: Peripartum Cardiomyopathy with Repetitive Ventricular Tachycardia. A 30-year-old asymptomatic pregnant woman at 38 weeks' gestation was noticed to have repetitive monomorphic ventricular tachycardia. A dilated left ventricle with moderately reduced systolic function was found on echocardiographic examination. To the best of our knowledge, a case of peripartum cardiomyopathy presenting with repetitive monomorphic ventricular tachycardia has not been previously reported.
Keywords: peripartum cardiomyopathy; ventricular tachycardia